1995
DOI: 10.1159/000244196
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol, Morphine and Barbiturate Alter the Hemodynamic and Cerebral Response to Cocaine in Newborn Pigs

Abstract: Newborns delivered to cocaine-abusing mothers are often exposed to other concurrently consumed illicit drugs, which may alter the hemodynamic and cerebral response to cocaine. This study examined the interaction of ethanol, morphine or barbiturate with cocaine on mean arterial pressure (MAP), cerebral blood flow (CBF) and cerebral metabolic rate of oxygen (CMRO2) in newborn pigs. CBF, CMRO2 and cerebral O2 extraction (CECO2) were measured before and 4 and 10 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…In studies of conscious ani mals, hypertension is frequently observed within 2 min of cocaine administration [11,21,23]. The 10% increase in mean arterial blood pressure that we observed is compara ble to our prior results [14], but it is less than the 50% increase reported in adult rats and dogs following cocaine administration [21,23], The inability of SCH23390 to block the pressor response to cocaine suggests that D| receptor activation does not play an impor tant role in the pressor response to cocaine in newborn piglets. This conclusion is consistent with studies in adult rats and dogs in which adrenergic stimulation has been shown to me diate the hypertensive response to cocaine [20,21], blood flow have shown cocaine to increase, decrease, or not change the cerebral blood flow [9][10][11]14].…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In studies of conscious ani mals, hypertension is frequently observed within 2 min of cocaine administration [11,21,23]. The 10% increase in mean arterial blood pressure that we observed is compara ble to our prior results [14], but it is less than the 50% increase reported in adult rats and dogs following cocaine administration [21,23], The inability of SCH23390 to block the pressor response to cocaine suggests that D| receptor activation does not play an impor tant role in the pressor response to cocaine in newborn piglets. This conclusion is consistent with studies in adult rats and dogs in which adrenergic stimulation has been shown to me diate the hypertensive response to cocaine [20,21], blood flow have shown cocaine to increase, decrease, or not change the cerebral blood flow [9][10][11]14].…”
Section: Discussionsupporting
confidence: 72%
“…Some of this variability in results may be due to differences in experi mental methodology and species studied. We have previously shown cocaine to not change global or regional cerebral blood (low in awake, acutely instrumented piglets [14]. In terestingly, unlike that earlier study, we ob served an increase in blood flow in the cere bellum with cocaine in our awake, chronically instrumented piglets.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations